Facile synthesis of cationic gold nanoparticles with controlled size and surface plasmon resonance. Issue 94 (28th September 2016) - Kim, Young-Kwan; Landis, Ryan F.; Huo, Shuaidong; Kim, Chang Soo; Vachet, Richard W.; Rotello, Vincent M.
Abstract : We present a facile seed-mediated growth strategy for the size-controllable synthesis of large cationic gold nanoparticles by utilizing a functional cationic thiol ligand as a stabilizer. Abstract : We present a facile synthetic strategy for large cationic gold nanoparticles by utilizing a cationic thiol ligand as a stabilizer for seed-mediated growth. The size and surface plasmon resonance property of the gold nanoparticles were successfully controlled with this strategy.